2018
DOI: 10.7196/samj.2018.v108i4.12830
|View full text |Cite
|
Sign up to set email alerts
|

Blood and virus detection on barber clippers

Abstract: Background.Bleeding from the popular clean-shave 'chiskop' haircut was recently reported as prevalent in South Africa (SA), a country with 6.9 million HIV-infected people. Objectives. To investigate the prevalence of barber hair clipper contamination with blood and HIV and hepatitis B viruses. Methods. Fifty barbers from three townships in Cape Town, SA, were invited to participate. One clipper from each barber was collected immediately after it had been used for a clean-shave haircut. Each clipper was rinsed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…This study revealed the risk of HBV transmission through clippers used in haircuts at barber shops. The sequences of HBV DNA retrieved from two of the clippers were closely related to the HBV sequences reported from the Gauteng province [294].…”
Section: South Africasupporting
confidence: 54%
“…This study revealed the risk of HBV transmission through clippers used in haircuts at barber shops. The sequences of HBV DNA retrieved from two of the clippers were closely related to the HBV sequences reported from the Gauteng province [294].…”
Section: South Africasupporting
confidence: 54%